TIPOMORFOLOGI KOTA TERNATE DALAM DINAMIKA STRUKTUR SPASIAL (Jurnal Arsitektur ARCADE, 2026)
This study examines the typomorphology of Ternate City within the dynamics of spatial structure. The study focuses on how historical layers, Sultanate culture, local values, geographic conditions, and modernization shape the physical form of the city. A qualitative descriptive method with a typomorphological approach is applied. The analytical units are based on Kevin Lynch's city image elements and Hamid Shirvani's urban design elements. The observation unit is the spatial structure of urban development, including historical spatial patterns, present zoning, building typology, landmarks, road networks, and the north-central-south growth pattern of Ternate. The findings show that Ternate develops as a layered island city. The historical structure concentrated along the eastern coast because of Mount Gamalama, coastal accessibility, slope conditions, defense networks, and trade routes. At present, North Ternate maintains strong Sultanate and adat identity, Central Ternate forms a transitional zone, and South Ternate shows stronger modern growth. Lynch's elements appear through coastal paths, cultural districts, historical landmarks, and urban edges shaped by mountain and sea. Shirvani's elements appear through land use transformation, building form and massing, circulation systems, preservation, and activity support. The study concludes that modernization in Ternate is adaptive. It does not erase local identity, but forms a layered spatial structure that connects historical morphology with contemporary urban needs
Keywords: typomorphology, urban identity, modernization